Nec vi nec insidiis, leo et draco: the Lion, the Dragon and the Triumph of Christ - Milinović, Dino (2009)
The article analyses the symbolic meaning of animals, in particular the lion and the dragon in relation to Christological and imperial symbolics in later Roman empire.
Rad je nastao prema predavanju na 2. međunarodnom skupu Centra za ikonografska istraživanja Filozofskog fakulteta u Rijeci (2008.).
Projekt MZOS
ENG